Lala Şahin Pasha and Lala Şahin Pasha Mosque of 1348 in Bursa’s Mustafakemalpaşa (Kirmasti) District - Sema Gündüz Küskü; Elif Soydan (Sanat Tarihi Yıllığı)
The Mustafakemalpaşa district of Bursa is one of the cities in Türkiye that have been on an important travel route since ancient times. The city was conquered in 1336, joining Ottoman lands and being given as property to Lala Şahin Pasha, who’d contributed to the conquest. The most important data regarding Lala Şahin Pasha is his waqfiya dating to 1348. According to this waqfiya, Lala Şahin Pasha also had a complex consisting of a mosque and zawiyas [lodges] built. After his death, Pasha’s tomb was also added to the complex. Although attention is drawn to the different opinions that exist about which structures made up the complex, it currently only stands with its mausoleum and minaret. Therefore, this article will first collect all information and documents about Lala Şahin Pasha and then attempt to clarify the issues regarding this Pasha’s patronage and the structures within the complex. Mustafakemalpasha Municipality started excavations in the area where the complex is located between the mausoleum and the minaret in 2015-2016 and unearthed some walls. However, the excavation was not completed. After the investigations this study performed in the area in 2019, traces of these walls, which had mostly been covered with grass and soil over time, were detected on the site and documented by taking measurements. The uncovered survey plan showed these ruins to present important data about the mosque of the complex that was unable to survive to the present. Therefore, another aim of the study is to make suggestions about the location and plan of the complex’s mosque in line with the determined data.